Internet surf and turf--revealed - Waxer, Barbara M. (Thomson Course Technology, 2006)
Make sure students understand whose turf they are on when they surf the Internet for media! This one-of-a kind book provides important, easy-to-understand information on copyright laws and the fair use doctrine as they relate to Internet media. Students will also learn how to search for public domain media